Stable characteristics of intrapopulation heterogeneity in virus-specific Th1 cells during chronic viral challenge infection - Plajer, Valerie; Madrigal-Avilés, Adrián; Dzamukova, Maria; Durán-Hernández, Nayar; Saikali, Philippe; Holecska, Vivien; Panse, Isabel; Lehmann, Katrin; Zhu, Jinfang; Mashreghi, Mir-Farzin; Hegazy, Ahmed N.; Peine, Caroline; et al. (Frontiers in Immunology, 2025)
Virus-specific CD4+ T cells typically undergo T helper (Th) 1 differentiation and contribute to a type 1 immune response in infection with lymphocytic choriomeningitis virus (LCMV). Using this model pathogen, we performed an in-depth analysis of the quantitative expression stability of the Th1 key transcription factor T-bet. Previously, it was shown that virus-specific Th1 cells arising in acute infections expressed T-bet at distinct intensities and maintained their T-bet expression differences after viral clearance as memory cells for weeks in the steady state. However, it was unclear whether differential T-bet expression was associated with heterogeneity inside the Th1 population and if the quantitative T-bet memory, particularly of those cells expressing T-bet at low levels, could withhold the strong and continuous stimulation present during chronic infection. Using T-bet-ZsGreen reporter mice, virus-specific Th1 cells were characterized phenotypically at protein, RNA, and DNA/chromatin accessibility levels. The Th1 cells arising during acute LCMV Armstrong infection showed a continuous spectrum of T-bet expression, ranging from cells with very high T-bet to cells with low T-bet. Even though the cells with low T-bet expression clearly possessed Th1 characteristics, they additionally showed certain T follicular helper (Tfh)-like features at protein and RNA level. When virus-specific Th1 cells were sorted according to T-bet-ZsGreen reporter expression intensity, adoptively transferred, and rechallenged by infecting the host animals with the chronic LCMV Clone 13 strain, they maintained quantitative differences in T-bet reporter and IFN-γ expression levels. The progeny of the former T-betlow cells still included a subpopulation with a mild Tfh-associated phenotype. Independent of their past and present T-bet expression level, all virus-reactive CD4+ T cells acquired phenotypic signs of exhaustion as characterized by upregulation of PD-1, LAG3, and TOX and vast absence of effector cytokine co-expression in the chronic infection environment. Collectively, our findings highlight the heterogeneity of T-bet+ antiviral CD4+ T cells and the stability of quantitative differences in individual virus-specific CD4+ T cells during chronic viral infection.